Gold Nanoparticles Based Enzyme Biosensor for the Detection of Chloramphenicol. (2017) - Sharma, Richa; Akshath, U.S.; Bhatt, Praveena; Thakur, M.S.; Raghavarao, K.S.M.S.
Abstract: Chronic use of chloramphenicol (CAM) antibiotic leads to anaemia and bone marrow suppression resulting in 40 – 50% mortality. Hence, there is a need to develop an economical, fast and convenient method to detect CAM in milk, honey, shrimp and other aquaculture products. In the current method, coenzyme A was used to indirectly quantify CAM (since it is the cofactor product of the acetylation reaction of CAM). Coenzyme A (CoASH) was used to stabilize gold nanoparticles which were characterized by studying their extinction spectra. The reductant concentration and synthesis time were optimized. With optimized parameters the proposed system could detect CoASH up to 0.1 nM in buffer, with a linear range of detection from 0.1 μM to 1 mM.